Identification of a novel 43-bp insertion in the heparan sulfate 6-O-sulfotransferase 3 (HS6ST3) gene and its associations with growth and carcass traits in chickens. Issue 3 (3rd July 2019) - Wang, Xiangnan; Li, Zhuanjian; Guo, Yaping; Wang, Yanbin; Sun, Guirong; Jiang, Ruirui; Kang, Xiangtao; Han, Ruili
Abstract: Previous studies have revealed a significant association between SNPs found within the heparan sulfate 6-O-sulfotransferase 3 ( HS6ST3 ) gene and obesity. This study identified a novel 43-bp indel polymorphism in intron 1 of HS6ST3 in 1963 chickens from nine different breeds, and three genotypes, designated II, ID and DD, were observed. The frequency of the 'I' (0.62–0.87) allele was higher than that of the 'D' (0.13–0.38) allele. A total of 777 individuals of the Gushi-Anka F2 resource population were used for the analysis of associations according to growth traits, carcass traits, serum variables and meat quality traits. The results showed that the 43-bp indel polymorphism was significantly associated with the body weight at 4 and 6 weeks of age, chest depth at 4 and 12 weeks of age and shank girth at 12 weeks of age ( P < 0.05). In terms of the carcass traits, the indel polymorphism was significantly associated with breast muscle weight, heart weight and leg weight (P < 0.05). These findings suggested that this indel polymorphism has the potential to become a new target for the marker-assisted selection of chicken growth and carcass traits.